ESRGAN untuk Memperbesar Resolusi pada Citra Bangunan - Sulaeman, Agus; Rauda Ramdania, Diena; Adzkia, Muhammad Fasya (The Indonesian Journal of Computer Science, 2022)
In the current era of technology, photos are an important existence for modern society where with photos we can get a lot of information. Quality photos must have a good resolution and level of sharpness, but sometimes the photos obtained are sometimes not satisfied, especially in the resolution section where there are some photos with low resolution. With the use of ESRGAN photos that have low resolutions can be increased so that the resolution without reducing the quality of the photo significantly.